ELECTRON MICROSCOPE STUDY OF THE DEVELOPMENT OF THE PAPILLOMA VIRUS IN THE SKIN OF THE RABBIT - Stone, Robert S. (The Rockefeller University Press, 1959)
Rabbit papilloma virus seems uniquely to begin its proliferation in the nucleolus of infected cells. In cells near the germinal layer of the stratum Malpighii spherical viral bodies seem to develop within a reticulum which forms out of the fine granular matrix of the nucleolus. The virus may later fill the nucleus and spread into the whole cell. The age of the cell, determined by its position in the Malpighian layer and by the extent of keratinization, can be correlated with the viral development.